Understanding coal miners' livelihood vulnerability to declining coal demand: Negative impact and coping strategies. (March 2020) - Wang, Delu; Wan, Kaidi; Song, Xuefeng
Abstract: Because of the significant declining in coal demand, the problem of miners' livelihood vulnerability is more and more serious. This study takes Ordos, the largest coal city in China, as its research area and uses the system dynamics method to construct a simulation model of miners' livelihood vulnerability. Further, the evolution of livelihood vulnerability in different scenarios is revealed and the effectiveness of different coping strategies is discussed. The results show a certain degree of volatility in miners' livelihood vulnerability in Ordos and a high overall level of vulnerability; compared with capacity reduction, the coal price slump has a greater negative impact on miners' livelihood. Second, there are clear differences in the overall and cumulative effects of different coping strategies. Compared with reducing enterprise tax rate and improving social security level, developing living service industry, enhancing financial service level, and improving the technology and education level have a more marked effect on reducing livelihood vulnerability; reducing enterprise tax rate can quickly reduce vulnerability, but its effectiveness is declining, while the cumulative effect of other strategies is increasing. Finally, strategies have different influence paths on miners' livelihood, and that is the main reason for the difference in the effectiveness of strategies. Highlights: A system dynamics model of the miners' livelihood vulnerability evolution in Ordos is constructed. The impacts of de-capacity and coal price slump on the miners' livelihood vulnerability are revealed. The differences in the overall and cumulative effects of different coping strategies are clarified. The main reasons for the difference in the effectiveness of coping strategies are discussed.